ANALISIS RELEVANSI LULUSAN PERGURUAN TINGGI DENGAN DUNIA KERJA - Muhson, Ali; Wahyuni, Daru; Supriyanto, Supriyanto; Mulyani, Endang (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2012)
Abstract: A Relevance Analysis of University Graduates with World of Work. Education should be oriented to the competencies required by the workforce as a percentage of unemployment among the educated increase continuously. This study aims to examine the relevance of YSU Economic Education graduates. The study only focuses on the type of work and subjects taught. The subject of this study is the alumni of Economic Education Study Program. Sampling technique used is snowball sampling. Data collection technique using questionnaires and documentation while the technique of data analysis using descriptive analysis. The result suggests that the majority of the graduates find their first job as private a teacher, a private employee and a tutor, while current job of the most graduates are private teacher, private employee, and civil servant (teacher). The data shows that more than 50 percent of the graduates work in the education area. This implies that the relevance level based on the type of work is categorized as sufficient. Majority of the graduates teaches social science, economic, and entrepreneurship, hence it can be concluded that the relevance level based on the subjects taught is highly relevant. Keyword: relevance of graduates, type of work, unemployment, employment Abstrak: Analisis Relevansi Lulusan Perguruan Tinggi dengan Dunia Kerja. Pendidikan harus berorientasi pada kompetensi yang dibutuhkan oleh dunia kerja karena persentase penganggur di kalangan terdidik terus meningkat. Penelitian ini bertujuan untuk mengkaji tingkat relevansi (kesesuaian) lulusan Pendidikan Ekonomi UNY. Kajian hanya diarahkan pada jenis pekerjaan dan mata pelajaran yang diampu. Penelitian ini mengambil subjek alumni Prodi Pendidikan Ekonomi dari berbagai angkatan. Teknik sampling yang digunakan adalah snowball sampling. Teknik pengumpulan data menggunakan angket dan dokumentasi sedangkan teknik analisis data menggunakan analisis deskriptif. Penelitian ini menemukan bahwa jenis pekerjaan pertama lulusan yang paling dominan adalah guru swasta, pegawai swasta dan tenaga pengajar/tentor, sedangkan jenis pekerjaan sekarang lulusan didominasi sebagai guru swasta, pegawai swasta dan guru negeri. Tingkat relevansi dilihat dari jenis pekerjaan termasuk kategori cukup karena separo lebih lulusan bekerja di bidang pendidikan, sementara itu jika dilihat dari mata pelajaran yang diampu juga sangat relevan karena sebagian besar alumni mengajar IPS, Ekonomi dan Kewirausahaan. Kata Kunci: relevansi lulusan, jenis pekerjaan, pengangguran